2013
DOI: 10.1021/ja4086484
|View full text |Cite
|
Sign up to set email alerts
|

Observing Assembly of Complex Inorganic Materials from Polyoxometalate Building Blocks

Abstract: Understanding the aqueous state of discrete metal-oxo clusters, prenucleation clusters, and even simple ions is valuable for controlling the growth of metal-oxide materials from water. Niobium polyoxometalates (Nb-POMs) are unique in the aqueous metal-oxo cluster landscape in their unusual solubility behavior: specifically, their solubility in water increases with increasing ion-pairing contact with their counterions, and thus provides a rare opportunity to observe these and related solution phenomena. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
71
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 104 publications
(75 citation statements)
references
References 61 publications
3
71
0
1
Order By: Relevance
“…Scattering data is dependent on form factors (size, shape, and scattering contrast) and structure factors (interactions between particles). 72 (2) Understanding the mechanism of linking clusters in solution (formation of macromolecular chains) by varying aqueous conditions. 71 This method transforms the reciprocal space data to real space and yields a geometrical representation of the scattering particle as a probability histogram ( p(r) vs. radius).…”
Section: Studying Clusters Via Saxsmentioning
confidence: 99%
See 1 more Smart Citation
“…Scattering data is dependent on form factors (size, shape, and scattering contrast) and structure factors (interactions between particles). 72 (2) Understanding the mechanism of linking clusters in solution (formation of macromolecular chains) by varying aqueous conditions. 71 This method transforms the reciprocal space data to real space and yields a geometrical representation of the scattering particle as a probability histogram ( p(r) vs. radius).…”
Section: Studying Clusters Via Saxsmentioning
confidence: 99%
“…75 (Fig. 72 This simple acidification of the cluster led to improved solubility behavior and better thin film quality in addition to providing the correct Li : Nb ratio for the targeted perovskite material. 76 This has inspired the investigation of their dimerization behavior in solution using SAXS.…”
Section: Studying Clusters Via Saxsmentioning
confidence: 99%
“…These are formed by metals (addenda atoms) such as tungsten, molybdenum and vanadium in their higher oxidation state; however, over the last decades, it has been shown that other metals can serve as the primary atoms within POM clusters, such as niobium [12,13], and tantalum [14,15]. POMs are composed of condensed metal-oxygen {MO x } polyhedra (x = 4 to 7).…”
Section: Pom-based Clusters and Supramolecular Aggregatesmentioning
confidence: 99%
“…[6] Tr aditionally,m etallophilic contacts exhibiting short metal-metal distances have been characterized in the solid-state by Xray crystallographic studies.M ore importantly,t he interactions in solution have been probed by spectroscopic methods (such as IR, Raman, UV/Vis,NMR, and ESR spectroscopies) and computational techniques have also been important in the study of such contacts. [7] Although small-angle X-ray scattering (SAXS) has been used extensively to probe the size,shape,and interactions of biomolecules, [8] prenucleation clusters, [9] discrete clusters, [10] and nanoparticles [11] in solution, metal-metal interactions have not been explored with this method. While the strong scattering between heavy metals is conducive to this technique,t he small size of molecular species renders interpretation of data challenging.H owever, understanding the relationship between structure in solids and solution is of paramount importance in understanding natural phenomena and controlling synthetic processes.…”
mentioning
confidence: 99%